2022
DOI: 10.3390/ijerph191711088
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Modifiable Risk Factors of Exacerbations in Chronic Respiratory Diseases with Airways Obstruction in Vietnam

Abstract: Objectives: to determine modifiable risk factors of exacerbations in chronic respiratory diseases with airways obstruction (i.e., asthma and COPD) in southern Vietnam. Methods: an environmental and health-related behavioural questionnaire was submitted to patients with both chronic respiratory symptoms and airways obstruction. An exacerbation was defined as any acute worsening in clinical symptoms requiring a change in treatment, in a patient receiving prophylactic therapy. Results: 235 patients were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thirdly, it has been demonstrated that influenza vaccination can also reduce flu-related acute-lower-respiratory infections in the elderly population and hospitalized patients [ 25 , 26 ]. Severe airflow limitation due to lower respiratory tract infection is also a risk factor for the exacerbation of chronic airway disease [ 27 , 28 ]. All these causes suggest a strong recommendation for influenza vaccination in elderly patients with chronic airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, it has been demonstrated that influenza vaccination can also reduce flu-related acute-lower-respiratory infections in the elderly population and hospitalized patients [ 25 , 26 ]. Severe airflow limitation due to lower respiratory tract infection is also a risk factor for the exacerbation of chronic airway disease [ 27 , 28 ]. All these causes suggest a strong recommendation for influenza vaccination in elderly patients with chronic airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…Việt Nam có 7% đến 10% dân số mắc COPD [7 -8]. Trong số các bệnh hô hấp mạn tính có tắc nghẽn đường thở tại TP.HCM, điều kiện sống và thói quen nguy cơ đã được mô tả: 68% bệnh nhân có thói quen hút thuốc lá, 66% phơi nhiễm nghề nghiệp; ô nhiễm không khí có liên quan đến nhà ở thông gió kém chiếm 71%; 40% có diện tích nhà ở trên đầu người ≤ 10 m 2 và 24% có hơn một đợt cấp trong vòng 12 tháng [9]. Việc xác định các yếu tố nguy cơ góp phần làm suy giảm CNHH sẽ giúp đề xuất các khuyến nghị nhằm tăng cường dự phòng cấp 3 của bệnh.…”
Section: đặT Vấn đềunclassified
“…Đây là nghiên cứu mô tả các trường hợp bệnh, phân tích dữ liệu thứ cấp, sử dụng dữ liệu từ một nghiên cứu đã công bố trước đó [9].…”
Section: đốI Tượng -Phương Phápunclassified
“…Seguindo a ordem cronológica das publicações, o artigo mais antigo incluído na presente revisão foi o deNguyen et al (2022). Os autores mostraram que além da cessação do tabagismo, são necessárias políticas mais favoráveis, incluindo a melhoria do ambiente ocupacional e das habitações para uma melhor ventilação, visando a prevenção da gravidade das doenças respiratórias crónicas.…”
unclassified